2021
DOI: 10.1093/advances/nmab075
|View full text |Cite
|
Sign up to set email alerts
|

Water Security and Nutrition: Current Knowledge and Research Opportunities

Abstract: Water is an essential nutrient that has primarily been considered in terms of its physiological necessity. But reliable access to water in sufficient quantities and quality is also critical for many nutrition-related behaviors and activities, including growing and cooking diverse foods. Given growing challenges to water availability and safety, including climate change, pollution, and infrastructure degradation, a broader conceptualization of water and its diverse uses is needed to sustainably achieve global n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 203 publications
(204 reference statements)
0
22
0
2
Order By: Relevance
“…In the end, it is clear from this empirical investigation that the water and nutrition nexus involves collaborations from several other sectors including agriculture, food, gender, public health, and political economy. A recent review study showed similar conclusions, namely that an interdisciplinary collaboration in the water–nutrition nexus is vital for ensuring equitable access to safe water and healthy foods [ 49 ].…”
Section: Discussionmentioning
confidence: 75%
“…In the end, it is clear from this empirical investigation that the water and nutrition nexus involves collaborations from several other sectors including agriculture, food, gender, public health, and political economy. A recent review study showed similar conclusions, namely that an interdisciplinary collaboration in the water–nutrition nexus is vital for ensuring equitable access to safe water and healthy foods [ 49 ].…”
Section: Discussionmentioning
confidence: 75%
“…These ndings are important because human behavior and health decision-making are largely driven by experiences, perceptions, and attitudes 3,20 . Individuals who perceive their water to be dangerous or of suboptimal quality are more likely to avoid or not pay for piped water 26,27 , consume bottled water 28,29 , and substitute sugar-sweetened beverages for water 23,30 , which in turn have negative consequences for the sustainability of water services as well as human and environmental well-being. Bottled water production, for instance, is a resource-intensive process that generates considerable greenhouse gas emissions and other contaminants that can pollute local water sources; it is also vastly more expensive than tap water and often of poorer quality [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although safe drinking water is fundamental for health and well-being 22,23 , experienced and anticipated drinking water harm have not been systematically captured in a globally comparable way. For example, progress toward Sustainable Development Goal 6.1, "ensure availability and sustainable management of water and sanitation for all," is tracked by the WHO/UNICEF Joint Monitoring Programme (JMP), which assesses the proportion of the population using a safely managed drinking water source.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately two billion people worldwide lacked access to safely managed drinking water in 2020 (3) , and approximately four billion face severe water scarcity at least one month out of the year (4) . The syndemicor cooccurring and mutually amplifyingrelationship between these two forms of insecurities has received growing attention (5)(6)(7)(8)(9) . Yet limited research has examined the ways in which cooccurrence of these two insecurities manifests across different populations (9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%